Ocorrência de anticorpos anti-Toxoplasma gondii, anti-Neospora caninum e anti-Leptospira spp. Em gambás (Didelphis spp.) no estado de São Paulo, Brasil - Horta, Mauricio Claudio (2016)
Opossum (Didelphis spp.) is an omnivorous marsupial native to the Americas that shows synanthropic behavior in urban areas. Despite its proximity to domestic animals and humans, knowledge of its participation in the epidemiology of some zoonotic agents is substantial. This study aimed to determine the presence of antibodies against Toxoplasma gondii, Neospora spp. and Leptospira spp. in blood samples collected from opossums in 18 municipalities in the state of São Paulo, Brazil, between 2003 and 2008. Blood samples from 343 opossums: Didelphis aurita (n = 256) and Didelphis albiventris (n = 87) were obtained. These were tested to detect antibodies against T. gondii, using the modified agglutination test (MAT-Toto; cutoff≥ 25); Neospora spp., using the indirect fluorescent antibody test (IFAT; cutoff≥ 25); and Leptospira spp., using the microscopic agglutination test (MAT-Lepto; cutoff≥ 100). Frequency of anti-T. gondii, Neospora spp. and Leptospira spp. antibodies were in 22.7%, 1.5% and 3.5%, respectively. The serogroups-serovars of Leptospira spp. presenting positive MAT-Lepto reactions were: Autumnalis-Butembo; Mini-Mini; Ballum-Castellonis; Icterohaemorrhagiae-Icterohaemorrhagiae; Icterohaemorrhagiae-Copenhageni and Grippotyphosa-Grippotyphosa or Bananal. This study demonstrated that these zoonotic agents are circulating in opossum populations in the state of São Paulo. Therefore, investigations regarding the role of marsupials in the epidemiology of each of these diseases should be conducted, especially to understand the behavior of these animals as zoonosis maintenance hosts.